2012
DOI: 10.1016/j.exger.2011.10.004
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNA changes in human arterial endothelial cells with senescence: Relation to apoptosis, eNOS and inflammation

Abstract: A senescent phenotype in endothelial cells is associated with increased apoptosis, reduced endothelial nitric oxide synthase (eNOS) and inflammation, which are implicated in arterial dysfunction and disease in humans. We tested the hypothesis that changes in microRNAs are associated with a senescent phenotype in human aortic endothelial cells (HAEC). Compared with early-passage HAEC, late-passage HAEC had a reduced proliferation rate and increased staining for senescence-associated beta-galactosidase and the t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
133
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 155 publications
(135 citation statements)
references
References 47 publications
2
133
0
Order By: Relevance
“…Many studies reported that miR‐221 and miR‐222 have the effect of promoting and/or inhibiting tumour angiogenesis in the malignant processes of HCC,62 breast cancer,63 lung cancer,64 human epithelial cancers,65 human glioblastoma,66 gastric cancer 67 and other various cancers 60, 61, 68, 69, 70, 71. MiR‐221 and miR‐222 inhibit angiogenesis by blocking tube formation, proliferation, migration and wound healing through repressing the expression of c‐Kit and endothelial nitric oxide synthase (eNOS) 24, 26, 72, 73. Moreover, they both suppress angiogenesis by reducing zinc finger E‐box binding homeobox 2 (ZEB2) in ECs 74…”
Section: Mirnas That Target Genes Involved In Angiogenesismentioning
confidence: 99%
“…Many studies reported that miR‐221 and miR‐222 have the effect of promoting and/or inhibiting tumour angiogenesis in the malignant processes of HCC,62 breast cancer,63 lung cancer,64 human epithelial cancers,65 human glioblastoma,66 gastric cancer 67 and other various cancers 60, 61, 68, 69, 70, 71. MiR‐221 and miR‐222 inhibit angiogenesis by blocking tube formation, proliferation, migration and wound healing through repressing the expression of c‐Kit and endothelial nitric oxide synthase (eNOS) 24, 26, 72, 73. Moreover, they both suppress angiogenesis by reducing zinc finger E‐box binding homeobox 2 (ZEB2) in ECs 74…”
Section: Mirnas That Target Genes Involved In Angiogenesismentioning
confidence: 99%
“…Endothelial cells transfected with miRs-221/222 showed a reduction in both eNOS protein level and release of NO 21 . However, the direct mechanism by which these miRs may exert that effect is unknown because there is no target region for miRs-221/222 in the NOS3 mRNA molecule generating a mRNA:miR interaction according to the predictive analysis by bioinformatics tools.…”
Section: Discussionmentioning
confidence: 99%
“…For instance, induced senescence in human ECs has been addressed to reduce expression levels of proliferation‐stimulating/apoptosis‐suppressing miR‐17–92, ‐21 and ‐214, in contrast to tumour suppressor p16 and miR‐222 family for suppression of endothelial nitric oxide synthase (eNOS) 23. Down‐regulation of miR‐126 and ‐130a, in particular, impairs EC proliferation, migration and angiogenesis.…”
Section: Ischaemia/hypoxia‐associated Mirna Signatures In Atherosclermentioning
confidence: 99%
“…Between them, miR‐126, ‐17–92 and ‐221 are most known to control the growth of new blood vessels 23.…”
Section: Mirna Signatures Related To Pathological Inflammatory Conditmentioning
confidence: 99%
See 1 more Smart Citation